Authors' attitudes to, and awareness and use of, a university institutional repository. - Watson, Sarah (United Kingdom Serials Group (UKSG), 2007)
This article reports the findings of an author study at Cranfield University. The study investigated authors' publishing behaviours, attitudes, concerns, and their awareness and use of their institutional repository (IR), Cranfield QUEprints. The findings suggest that despite a reasonable amount of advocacy many authors had not heard of QUEprints and were not aware of its purpose. Once explained, all authors saw at least one benefit to depositing a copy of their work to QUEprints, but many were unsure how to deposit, preferring to depend on the Library to do the work. The authors voiced few concerns or conditions regarding the inclusion of their work in QUEprints, but felt that it would be an extra, inconvenient step in their workload. This research led to the development of the Embed Project which is investigating how to embed the IR into the research process and thereby encourage more authors to deposit their work.